EFFECTIVENESS OF SMART SPACE MEDIA-ASSISTED CONTENT MASTERY SERVICES TO IMPROVE CLASS ILLIM IN STUDENT LEARNING AT SMAN 14 JAMBI CITY - Cinta, Cinta Aulia Aziz; Rasimin, Rasimin; Yusra, Affan (Jurnal Kopendik, 2025)
An unconducive classroom climate at SMAN 14 Jambi City has affected students’ motivation and participation in learning. This study aims to examine the effectiveness of content mastery services assisted by Smart Space media in improving classroom climate. Using a quantitative approach with a one-group pretest–posttest design, the study involved 20 students of class X E5. Data were collected through questionnaires and analyzed using normality and t-test analyses. The results showed a significant improvement in the classroom climate after the intervention, indicating that the integration of interactive digital media in guidance and counseling services effectively enhances the learning atmosphere. These findings highlight that technological innovation in counseling services can foster students’ cognitive, affective, and social development. It is recommended that guidance and counseling teachers systematically utilize digital media to build a positive classroom climate and support school policies that promote technology-based educational practices.